Knowledge, attitudes and practices towards COVID-19 among multiethnic elderly Asian residents in Singapore: a mixed-methods study - Amudha Aravindhan; Alfred Tau Liang Gan; Ester Pei Xuan Lee; Preeti Gupta; Ryan Man; Kam Chun Ho; Sharon Cohan Sung; Ching-Yu Cheng; Moi Lin Ling; Hiang Khoon Tan; Tien Yin Wong; Eva Katie Fenwick; et al. (Singapore Medical Journal)
Introduction: We investigated the knowledge, attitudes and practice (KAP) towards coronavirus disease 2019 (COVID-19) and its related preventive measures in Singaporeans aged ≥60 years. Methods: This was a population-based, cross-sectional, mixed-methods study (13 May 2020–9 June 2020) of participants aged ≥ 60 years. Self-reported KAP about ten symptoms and six government-endorsed preventive measures related to COVID-19 were evaluated. Multivariable regression models were used to identify sociodemographic and health-related factors associated with KAP in our sample. Associations between knowledge/attitude scores and practice categories were determined using logistic regression. Seventy-eight participants were interviewed qualitatively about the practice of additional preventive measures and data were analysed thematically. Results: Mean awareness score of COVID-19 symptoms was 7.2/10. The most known symptom was fever (93.0%) and the least known was diarrhoea (33.5%). Most participants knew all six preventive measures (90.4%), perceived them as effective (78.7%) and practised ‘wear a mask’ (97.2%). Indians, Malays and participants living in smaller housing had poorer mean scores for knowledge of COVID-19 symptoms. Older participants had poorer attitudes towards preventive measures. Compared to Chinese, Indians had lower odds of practising three out of six recommendations. A one-point increase in score for knowledge and attitudes regarding preventive measures resulted in higher odds of always practising three of six and two of six measures, respectively. Qualitative interviews revealed use of other preventive measures, for example, maintaining a healthy lifestyle. Conclusions: Elderly Singaporeans displayed high levels of KAP about COVID-19 and its related preventive measures, with a positive association between levels of knowledge/attitude and practice. However, important ethnic and socioeconomic disparities were evident, indicating that key vulnerabilities remain, which require immediate attention.